Benteler Vehicle Dynamics -- Fahrdynamikentwicklung basierend auf einer neuen Auslegungstheorie - Kohl, Sergej; Sextro, Walter; Zuber, Armin (8. Tag des Fahrwerks, Aachen, 2012)

Piezoelectric applications of hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics - Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
A hydrothermal method utilizes a crystallization process in the solution so that the pure and high-quality powders can be realized. Sintering from the hydrothermal KNbO3 and NaNbO3 powders, a high-dense lead-free piezoelectric (K,Na)NbO3 ceramics could be obtained (density: 98.8%). Concerning about the g33 constant, high value as large as commercial PZT ceramics was measured. Therefore, the hydrothermal (K,Na)NbO3 ceramics is usable for the sensors and the energy harvesting devices. To demonstrate the (K,Na)NbO3 ceramics, a hydrophone sensor was fabricated and evaluated.
Keywords: crystallisation; hydrophones; piezoceramics; potassium compounds; powder technology; powders; sensors; sintering; sodium compounds; (K0.48Na0.52)NbO3; KNbO3 powder; NaNbO3 powder; crystallization; energy harvesting devices; g33 constant; hydrophone sensor; hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics; hydrothermal method; piezoelectric applications; sintering; Materials; Transducers

Piezoelectric Properties of Li-Doped (K0.48Na0.52)NbO3 Ceramics Synthesized Using Hydrothermally-Derived KNbO3 and NaNbO3 Fine Powders - Maeda, Takafumi; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
[$Li_x(Na_0.52K_0.48)_1-x]NbO_3 (0 ≤ x ≤ 0.091)$ ceramics were synthesized using hydrothermal powders and the lithium doping content was controlled to optimize their piezoelectric properties. The raw KNbO$_3$ and NaNbO$_3$ powders were obtained separately by a hydrothermal method and LiNbO$_3$ powders were prepared by milling a commercial LiNbO$_3$ single crystal. These powders were mixed with ethanol at a molar ratio LiNbO$_3$: ($Na_0.52K_0.48$)NbO$_3 = x : 1-x$. The synthesized powders were sintered at 1060--1120 $\,^{°}$C for 2 h. We succeeded in obtaining highly dense [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$ ceramics using hydrothermal powder. The X-ray diffraction patterns revealed that the crystal phase changed from orthorhombic to tetragonal at around x = 0.06. At this morphotropic phase boundary (MPB), the c/a ratio changed from 1.016 to 1.024 and the highest piezoelectric constant was obtained with the chemical component of [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$. The obtained piezoelectric properties were as follows: $k_33 = 0.51, ε 33^T/ ε _0 = 836$ , $c_33^E = 46$ GPa, $d_33 = 203$ pC/N, and $T_c = 482 $\,^{°}$C$.

Conceptual Design of Advanced Condition Monitoring for a Self-Optimizing System based on its Principle Solution - Sondermann-Wölke , Christoph; Meyer, Tobias; Dorociak, Rafal; Gausemeier, Jürgen; Sextro, Walter (Proceedings of the 11th International Probabilistic Safety Assessment and Management Conference (PSAM11) and The Annual European Safety and Reliability Conference (ESREL2012))
The rapid development of communication and information technology opens up fascinating perspectives, which go far beyond the state of the art in mechatronics: mechatronic systems with inherent partial intelligence. These so called self-optimizing systems adapt their objectives and behavior autonomously and flexibly to changing operating conditions. On the one hand, securing the dependability of such systems is challenging due to their complexity and non-deterministic behavior. On the other hand, self-optimization can be used to increase the dependability of the system during its operation. However, it has to be ensured, that the self-optimization works dependable itself. To cope with these challenges, the multi-level dependability concept was developed. It enables predictive condition monitoring, influences the objectives of the system and determines suitable means to improve the system's dependability during its operation. In this contribution we introduce a procedure for the conceptual design of an advanced condition monitoring based on the system's principle solution. The principle solution describes the principal operation mode of the system and its desired behavior. It is modeled using the specification technique for the domain-spanning description of the principle solution of a self-optimizing system and consists of a coherent system of eight partial models (e.g. requirements, active structure, system of objectives, behavior, etc.). The partial models are analyzed separately in order to derive the components of the multi-level dependability concept. In particular, the reliability analysis of the partial model active structure is performed to identify the system elements to be monitored and parameters to be measured. The principle solution is extended accordingly: e.g. with system elements required for the realization of the dependability concept. The advantages of the method are shown on the self-optimizing guidance module of a railroad vehicle.
Keywords: Mechatronic Systems; Principle Solution; Condition Monitoring; Conceptual Design

Analysis of different operation modes for inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2012 Conference Proceedings)
Piezoelectric inertia motors, also known as ``stick-slip-drives'', use the inertia of a body to drive it by means of a friction contact in small steps. While these steps normally involve stiction and sliding, the motors can also operate in ``slip-slip'' mode without any phase of static friction. In this contribution, a one degree of freedom model of an inertia motor driven by an ideal actuator is analysed. Start-up and constant velocity operation of the motor are investigated and appropriate quantities to compare ``stick-slip'' and ``slip-slip'' operation are determined. Different aspects such as velocity, uniformity of motion, load capacity, robustness, efficiency, and wear are considered. The analysis allows both modes to be applied advantageously in different applications and can widen the field of application of piezoelectric inertia motors. Motor designers are enabled to choose the appropriate mode of operation and the best drive parameters for their individual applications.
Keywords: Piezoelectric Inertia Motors; Drive Signals; Stick-slip; Slip-slip

Biomimetic approaches to create anti-reflection glass surfaces for solar cells using self-organizing techniques - Achtelik, J.; Sievers, W.; Lindner, Jörg (Materials Science and Engineering: B)
Aiming to diminish the reflection losses of glass covered light harvesting devices, the optical reflectivity of nanostructured glass surfaces is studied theoretically and experimentally. The work is inspired by the nanoscale roughness of insect eyes, which is tried to be replicated on a technical glass surface. To this end, the reflectivity of glass surfaces with topographies represented by linear, parabolic and Fermishaped glass/air fill factor profiles is calculated for normal incidence. It is shown that using the latter ones, an almost complete suppression of reflections can be achieved. A simple, self-organization technique to create such Fermi-shaped filling factor profiles in glass experimentally is also presented.

Self-Organized Nanostructure Formation for Anti-Reflection Glass Surfaces - Achtelik, Jörn; Kemper, Ricarda M.; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
Two methods to create biomimetic anti-reflection nanostructures in ordinary glass microscope object slides are presented. One technique is based on a nanosphere lithography process combined with physical vapour deposition of nickel and reactive ion etching (RIE). The other uses plasma induced dewetting of a smooth nickel surface. The amount of reflected light was measured and a method to simulate the reflectivity from an atomic force microscopy (AFM) topography scan of the glass surface is presented. The reflectivity for visible light at normal incidence was reduced to 20-50 % of the original value with both methods and the simulation gives results in good agreement to the measurement.

Gyrotropic Metamaterials - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Formation of defects in cubic GaN grown on nano-patterned 3C-SiC (001) - Kemper, R. M.; Häberlen, M.; Schupp, T.; Weinl, M.; Bürger, M.; Ruth, M.; Meier, Cedrik; Niendorf, T.; Maier, H. J.; Lischka, K.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report an anisotropic formation of defects in cubic GaN grown on nano-patterned 3C-SiC/Si (001) by molecular beam epitaxy. Nano-patterning of 3C-SiC/Si (001) is achieved by nanosphere lithography and a reactive ion etching process. Atomic force microscopy and scanning electron microscopy show that the selectivearea- grown cubic GaN nucleates in two structurally different domains, which most probably originate from the substrate. In adjacent domains the formation of defects, especially hexagonal inclusions, is different and leads to two different surface morphologies. The dominant phase within these domains was measured by electron backscatter diffraction. Optical properties were investigated by micro-photoluminescence and cathodoluminescence spectroscopy.

TEM investigation of GaN thin films grown on nanostructured 3C-SiC/Si(001) substrates - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; Tillmann, K.; Riedl, Thomas; As, Donald; Lindner, Jörg

Nanosphere Lithography: State-of-the-art and Future Directions - Lindner, Jörg

TEM Characterization of Nickel Nanodot Arrays on Silicon formed by Nanosphere Lithography - Pauly, Johannes; Lindner, Jörg

Nanokugellithographie: Grundlagen und Anwendungen - Lindner, Jörg

Nanolithographie von Oberflächen für das Wachstum optoelektronischer Strukturen - Lindner, Jörg

Dual-polarity plasmonic metalens for visible light - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

Optical properties of cubic GaN from 1 to 20 eV - Feneberg, Martin; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schörmann, Jörg; Schupp, Thorsten; As, Donat Josef; Hörich, Florian; Bläsing, Jürgen; Krost, Alois; Goldhahn, Rüdiger (Physical Review B)

Vibrational fingerprints of LiNbO3-LiTaO3 mixed crystals - Sanna, Simone; Riefer, Arthur; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (Proceedings of ISAF-ECAPD-PFM 2012)
The structural and vibrational properties of lithium niobate (LN) – lithium tantalate (LT) mixed crystals (LNT, LiNb1-xTaxO3) are investigated over the whole composition range by first-principles simulations. The crystal volume grows roughly linearly from LT to LN, whereby the lattice parameters a and c show minor deviations from the Vegard behavior between the end compounds, LiNbO3 and LiTaO3. Our calculations in the framework of the density functional theory show the TO1, TO2 and TO4-modes to become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. The frequency shifts of the zone center A1-TO phonon modes for crystals with different compositions are found to be as large as 30 cm-1. Raman spectroscopy, which is sensitive to the A1 modes, can be therefore employed to determine the crystal composition.
Keywords: Ferroelectrics; Vibrational properties; LiNbO3; LiTaO3; Mixed Crystals

Coherent optoelectronics with quantum dots - Michaelis de Vasconcellos, Steffen; Gordon, Simon; Mantei, Dirk; Leier, Yves Alexander; Al-Hmoud, M.; Quiring, Wadim; Zrenner, Artur (QUANTUM OPTICS WITH SEMICONDUCTOR NANOSTRUCTURES)
Coherent physics and applications of exciton qubits in electric fi eld tunable quantum dot structures are our focus. Excitations with picosecond (ps) laser pulses result in qubit rotations. Using state projection by tunnelling the readout can be performed in quantitative way. As a function of electric fi eld induced detuning Ramsey fringes of a single exciton qubit can be observed and controlled for double pulse excitation. Therefore it is possible to demonstrate voltage controlled qubit manipulations within a wide range of pulse delays. Using fast electric signals, phase-locked to ps-laser pulses, the coherent control of an exciton qubit can be obtained by electric interaction. Such voltage controlled qubit manipulations seem to be essential for new types of optoelectronic quantum gates and novel applications in the fi eld of coherent optoelectronics.
Keywords: excitons; quantum bits; coherent manipulation; Ramsey interference; quantum gate

A Method for Selectively Designing Modeling Languages for Product-Service Systems - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Modeling for Decision Support in Network-Based Services: The Application of Quantitative Modeling to Service Science)

Ansätze zur methodischen Unterstützung der Konstruktion von Produktivitätsmodellen für die Data Envelopment Analysis --- Entwicklung eines Softwareprototypen zur Umsetzung und Evaluation - Becker, Jörg; Knackstedt, Ralf; Beverungen, Daniel; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans (Service Engineering --- Management)